2014
DOI: 10.1038/srep05836
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond Pulsed Electric Fields (nsPEFs) Regulate Phenotypes of Chondrocytes through Wnt/β-catenin Signaling Pathway

Abstract: Nanosecond pulsed electric fields (nsPEFs) characterized by high voltage, low energy and non-thermal effects, have been broadly investigated as a potential tumor therapy; however, little is known about their effects on somatic cells. In this current study, we evaluated effects of nsPEFs on the phenotype of chondrocytes (morphology, glycosaminoglycan (GAG) content, proliferation and gene expression) and explored the mechanisms involved. Our results demonstrated that exposing chondrocytes to nsPEFs led to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 55 publications
1
57
0
Order By: Relevance
“…PES activates MAPK signaling pathway. PES not only upregulates phosphorylation of ERK and p38 (Zhao et al, 2006), but can also activate JNK, another member of the MAPK family, with fast increased phosphorylation level within minutes, which then decreases within 1 h (Morotomi-Yano et al, 2011a;2011b). As the signaling pathways activated by PES may become inactivated within minutes or hours, the effect caused by PES may last for minutes, hours, or days.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…PES activates MAPK signaling pathway. PES not only upregulates phosphorylation of ERK and p38 (Zhao et al, 2006), but can also activate JNK, another member of the MAPK family, with fast increased phosphorylation level within minutes, which then decreases within 1 h (Morotomi-Yano et al, 2011a;2011b). As the signaling pathways activated by PES may become inactivated within minutes or hours, the effect caused by PES may last for minutes, hours, or days.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Studies of neurodegenerative diseases have demonstrated that the Wnt/β-catenin signaling pathway regulates the proliferation and differentiation of neural stem cells and their precursor cells in the spinal cord (16,17). in addition, animal models of spinal cord injury have indicated that ES influences the proliferation and directional migration of nerve cells via the Wnt/β-catenin signaling pathway (18)(19)(20). In the field of oncology, it has been demonstrated that inhibition of the Wnt signaling pathway can lead to inhibition of cell proliferation and cell cycle, as well as the expression levels of β-catenin, which are associated with the activation and shutdown of Wnt signaling that regulates expression levels of downstream target genes, such as cyclin d1, c-myc, e-cadherin and lgr5, at the transcriptional level, thereby influencing the progression of tumors (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to EFs, electromagnetic fields (EMFs) have been applied in in vivo and in vitro studies using cartilage and growth plate explants, and tridimensional structures (Table 4-2) [151], [152], [154], [165], [170], [172], [184]. Similar to EFs, the technique of deliver EMFs consists of an indirect coupling system that uses external parallel coils connected to a function generator (Figure 4-1B) [152], [153], [163], [184].…”
Section: Electromagnetic Fieldsmentioning
confidence: 99%
“…The application of EMFs in monolayer cultures have shown preservation of chondrocytes morphology [153], increased DNA synthesis [160], and enhancement of proliferation and GAGs synthesis in human chondrocytes [192]. It has also been demonstrated that EMFs significantly increase cell population but decrease the synthesis of characteristic molecules of hyaline cartilage such as collagen type II, aggrecan, SOX-9, and GAGs [154].…”
Section: In Vitro Studies Using Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation